DEVELOPING INTERCULTURAL COMPETENCIES FOR TEACHERS IN THE PHILIPPINES - ARABIT-ZAPATOS, MA. LORELLA C. (2019)
This dissertation entitled, Developing Intercultural Competencies for Teachers in the Philippines" was conducted for the purpose of providing a model framework of intercultural competencies for teachers. The qualitative method was employed using the case study design which served as the basis in the validation and verification of the Model of Intercultural Competencies for Teachers. This research also discussed the teachers experiences in teaching the indigenous learners enrolled in mainstream schools. From the gathered data, the researcher developed intercultural competencies that became the basis for the design and development of Model of Intercultural Competencies for Teachers in the Philippines. The results of the study indicated that teaching the indigenous learners were challenging and fulfilling at the same time. The teachers in general found the experiences as challenging because of lacking intercultural competencies and fulfilling when they were able to overcome such difficulties in teaching indigenous learners. The teacher participants reiterated the importance of being culturally competent in order to address the needs of the indigenous learners. The researcher developed 5 major components of Intercultural Competencies namely; Pagkamulat or Cultural Awareness, Pakikipamuhay or Cultural Immersion, Pagkamaalam vii or Cultural Knowledge, Pagtuturo na may Pag-angkop ng Kaligirang Pang-edukasyon ng mga Katutubo or Teaching as Adaptation to the Learning Environment of the IP, Pagsulong at Pagtaguyod ng Karapatan ng Katutubo Bilang Adbokasiya of Advancing and Upholding the Rights of Indigenous Education. The Developed Intercultural Competencies for teachers can help in determining the teacher's readiness to teach and handle indigenous learners. The Developed Model of Intercultural Competencies for Teachers is developmental and progressive in nature. This means that the teacher may evolve or not from a least competent to highly intercultural competent teacher. Therefore the progress of the teacher also depends on the Department of Education and Commission on Higher Education programs and policies in order to capacitate and prepare the teachers. The study recommends to Review the existing Policies, Standards and Guidelines in Professional Education courses especially the Bachelor in Elementary Education, Bachelor in Early Childhood Education and Special Education. Revise in order to prepare the pre-service teachers in teaching indigenous teachers. Second to explore ways on how to provide trainings and seminars to the in-service teachers to enhance their Intercultural Competencies.